2018
DOI: 10.1039/c8dt02117a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable morphologies, multicolor properties and applications of RE3+ doped NaY(MoO4)2 nanocrystals via a facile ligand-assisted reprecipitation process

Abstract: Rare earth (RE3+)-doped NaY(MoO4)2 nanocrystals are efficient materials for realizing multicolor emission, which plays an important role in displays, W-LEDs, solar cells and biolabeling. Up to now, research on the multicolor tuning properties of RE3+-doped NaY(MoO4)2 nanoparticles has mostly focused on traditional preparation routes such as the hydrothermal method and sol-gel process. However, the products obtained using these methods are usually large in size (on the micron/submicron scale) and agglomeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…More recently Ding et al . synthesized high‐quality RE‐doped NaY(MoO 4 ) 2 NCs using a ligand‐assisted reprecipitation strategy . The ET mechanism from Tb 3+ to Eu 3+ in the NaY (MoO 4 ) 2 host was observed and colour tuning could be achieved by adjusting the concentrations of Tb 3+ and Eu 3+ .…”
Section: Development Of New Phosphorsmentioning
confidence: 99%
“…More recently Ding et al . synthesized high‐quality RE‐doped NaY(MoO 4 ) 2 NCs using a ligand‐assisted reprecipitation strategy . The ET mechanism from Tb 3+ to Eu 3+ in the NaY (MoO 4 ) 2 host was observed and colour tuning could be achieved by adjusting the concentrations of Tb 3+ and Eu 3+ .…”
Section: Development Of New Phosphorsmentioning
confidence: 99%
“…Lanthanide (Ln)-doped double sodium rare-earth (RE) molybdates (NaRE(MoO 4 ) 2 ) have been the subject of increasing interest during the last few years due to their interesting luminescence properties, which make them useful for many applications in different fields such as catalysis, 1 lighting, [2][3][4] thermometry, 5 ionic conductivity, 6 and bioimaging. 7,8 Focusing on the latter application, the high atomic number (Z) of Ln confers to the NaRE(MoO 4 ) 2 compounds a strong capacity for X-ray attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from solar energy, hydrogen energy is considered to be the second most important source of clean, renewable energy. , Photocatalysis and photoelectrochemical water electrolysis can provide an efficient and economical pathway toward solar hydrogen generation from water while leaving behind a low carbon footprint. Since the discovery of semiconductor photolysis of water using TiO 2 by Fujishima and Honda, research on efficient nanostructured semiconductors has reached widespread attention in the scientific community, especially in the past few decades, after the advent of advanced and improved cutting-edge nanofabrication techniques. − Transition-metal oxides have seen an upsurge in this research field, primarily because of their desirable properties, such as low cost, abundance, stability, ease of synthesis, and impressive photocatalytic performance. − An extensive range of metal oxides has been explored over the years, such as TiO 2 , SnO 2 , WO 3 , Fe 2 O 3 , and many synthetic strategies have been employed, such as morphology control, doping, design of efficient heterojunctions, and crystal facet engineering, to improve photoelectrochemical performance. ,− In this field of work, spinels have gained a strong foothold, because of their high stability on alkaline media, desirable bandgap, low cost, efficient electron transport, and photoexcited charge carrier generation properties. − Many spinel ferrites have been explored for photoelectrochemical and photocatalytic water splitting in recent times, the most popular being NiFe 2 O 4 , CoFe 2 O 4 , and CuFe 2 O 4 . − Dillert et al and Zhao et al have beautifully reviewed the application of ferrites in photocatalysis and photoelectrochemical water splitting and emphasized structural properties and experimental investigations of ferrites. Yin et al showed the effect of transition-metal doping in hematite nanoparticles to form spinel ferrites and found an enhancement in charge carrier density and photoelectrochemical performance.…”
Section: Introductionmentioning
confidence: 99%